Wakaf Hak Merek Dalam Sudut Pandang Islam - Ulfatussofa Miftah (Prodi Ekonomi Syariah Universitas Majalengka, 2022)
A brand is a basic element of the Intellectual Property Code that serves as a means to verify the identity, characteristics, and general nature of the product or service that the code subject has created. Law Number 20 of 2016 concerning Marks and Geographical Indications in Article 41 paragraph 1 states that there are several methods that can be used to transfer ownership of a mark, one of which is by implementing waqf. However, the article only explains the requirements and procedures for the transfer of a mark in the form of waqf which must be met in general and not to a specific one. This research includes literature research because it seeks to collect and analyze data or literature on brand rights waqf from an Islamic point of view. The results of this study indicate that the waqf of trademark rights according to the Islamic view, although there are no arguments or hadiths that specifically regulate it, according to Wahbah Al-Zuhayli it can refer to the arguments related to maslahah mursalah. In addition, according to Malikiyah trademark rights waqf can be classified as waqf with a period of time (muaqqat), which provisions have been regulated in the law.